Effect of non-hydrogen peroxide on antibacterial activity of Malaysian Meliponini honey against Staphylococcus aureus - Fatima Ibrahim Jibril; Abu Bakar Mohd Hilmi; Sani Aliyu (Wolters Kluwer Medknow Publications, 2020)
Introduction: Stingless bee is an insect that belongs to the family Apidae. Its name is based on its disability of stinging. It has a high product of Meliponini honey and propolis by which are commonly referred to as stingless bee honey and stingless bee propolis. Meliponini honey is one of the crucial natural sources and has the potential to kill infectious microorganisms. Previous studies have proved that the antibacterial activity of natural honey was an effect of hydrogen peroxide, a substance contained in the honey. However, these claims were contradicting with too many studies. Objective: Therefore, this study aimed to identify the antibacterial activity of Malaysian Meliponini honey which contained non-hydrogen peroxide against Staphylococcus aureus, an opportunistic microbial. Materials and Methods: Meliponini honey was used as an antibacterial agent for the treatment of S. aureus in agar well diffusion assay. An amplex red hydrogen peroxide kit was used to identify the hydrogen peroxide in the honey sample. Meanwhile, non-hydrogen peroxide activity was performed by using honey-catalase treated. Results: For the first time, we found that hydrogen peroxide was absent in all Meliponini honey samples. Meliponini honey has higher antibacterial activity (13.30 ± 0.56 mm) compared to Apis honey (9.03 ± 0.22 mm) in agar well diffusion assay. Discussion: Non-hydrogen peroxide in Meliponini honey is a bioactive compound and beneficial to kill the microbial infection. Conclusion: Antibacterial activity of Malaysian Meliponini honey is directly contributed by non-hydrogen peroxide.